2022
DOI: 10.1021/acs.jpclett.2c00316
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Entropic Excluded Volume Effects Driving Crowding-Induced Collapse and Folding of a Disordered Protein

Abstract: We investigate the conformational properties of the intrinsically disordered DNA-binding domain of CytR in the presence of the polymeric crowder polyethylene glycol (PEG). Integrating circular dichroism, nuclear magnetic resonance, and single-molecule Forster resonance energy transfer measurements, we demonstrate that disordered CytR populates a well-folded minor conformation in its native ensemble, while the unfolded ensemble collapses and folds with an increase in crowder density independent of the crowder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…By introducing the interaction between CytR and its partner DNA, the model successfully describes how, as the partner DNA approaches CytR, the free-energy landscape of CytR in the disordered state with multiple local minima changes into a landscape with a global minimum corresponding to the DNA-bound form of CytR [111,139]. Furthermore, the free-energy landscapes of CytR in the presence of a polymeric crowder, polyethylene glycol (PEG), mimicking crowded intracellular environments, provide a PEG concentration-temperature phase diagram showing that CytR is more folded both at lower temperatures and at higher PEG concentrations, which is in agreement with experimental results [140].…”
Section: Intrinsically Disordered Proteinssupporting
confidence: 86%
“…By introducing the interaction between CytR and its partner DNA, the model successfully describes how, as the partner DNA approaches CytR, the free-energy landscape of CytR in the disordered state with multiple local minima changes into a landscape with a global minimum corresponding to the DNA-bound form of CytR [111,139]. Furthermore, the free-energy landscapes of CytR in the presence of a polymeric crowder, polyethylene glycol (PEG), mimicking crowded intracellular environments, provide a PEG concentration-temperature phase diagram showing that CytR is more folded both at lower temperatures and at higher PEG concentrations, which is in agreement with experimental results [140].…”
Section: Intrinsically Disordered Proteinssupporting
confidence: 86%
“…The absolute heat capacity profile of CytR-DBD under low salt conditions displays a broad transition with no excess heat capacity peak . A variable-barrier model analysis of the thermogram demonstrated that the thermal transition occurs as a barrier-less process rather than a barrier-limited transition . The thermally unfolded state of CytR-DBD is highly collapsed and is distinct from the unfolded ensemble at room temperature.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in unfolded state dimensions at higher urea concentrations is also commonly observed in the unfolded state of many proteins, which could be attributed to the reduction of the hydrophobic effect (as water is a poor solvent). , In addition, the changes in chain dimensions are typically associated with the gradual loss of residual secondary structure content. We reported recently that molecular crowding induced by crowding agents like polyethylene glycol (PEG) causes gradual compaction of the unfolded state of CytR-DBD . Taken together, the unfolded state of CytR-DBD is sensitive to changes in solvent conditions, which proves that the balance between various intraprotein and protein–water interactions determines the dimension of the CytR-DBD unfolded state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations